Condiciones de Beck-Chevalley (2011)
En muchos marcos categóricos se presentan tránsitos entre los diferentes niveles de transferencia inmersos en las teoría de categorías. Los estudios adelantados por Grothendieck sobre pseudo-funtores permite estudiar muchos de estos tránsitos. En este trabajo se estudian condiciones de coherencia en estos procesos dinámicos, estas condiciones se hacen presentes en diversos marcos categóricos, algunas de ellas son llamadas las condiciones de Beck-Chevalley. / Abstract. The dynamics among diferent levels of transfer (morphism, functor and natural transformation) has been the subject of several studies, including a condition that relate this transfer levels. These studies have been presented in local spaces, ie specific categories. One of these conditions is called Beck-Chevalley conditions. Our main interest is show categorical frameworks in which these conditions appear naturally. This work want to illustrated this conditions through examples. And how the Beck-Chevalley conditions are presented in some of these frameworks particulary: categorical fibrations, lattices and topois.